Life cycle analysis of beverage packaging - Azman, Azmiza Idayu (2023)
Plastic has become a vital role in our daily life where most of the products surrounding us now are mostly made of plastic. For example television frames, shampoo bottles, tables, and others. Plastic also has become the main material for food and item packaging due to its lightweight characteristic. It will able to take up less space which means lighter loads for planes and trucks and lower emissions during transportation. However, it has been alarming concerns over the past years since the large-scale introduction of plastic after the Second World War, a total of 8.3 billion metric tons have been produced. Conventional plastic will take time to decompose approximately 450 years. Hence, it is predicted that in 2050, there will be about twelve billion tons of plastic in landfill and the environment e.g., the ocean. More plastic will be thrown away than those that people manage to clean up, even though they have tried their best. The purpose of this project is to select and compare the environmental impact of the packaging design of several consumer products using life cycle analysis software (LCA). It is software that is widely used to support sustainable development and a modeling tool to assess environmental impacts related to a product during its entire lifespan: from raw material extraction through processing, manufacturing, distribution, use, and disposal or recycling. Based on the openLCA free software, three beverage packaging were compared: plastic bottle, glass bottle and aluminium can. In order to obtain the result, the life cycle inventory (LCI) need to be identified based on case study, literature review and relevant assumptions. Then each of the beverage packaging flows, processes, product systems were also required to be identified in order able to run the openLCA software. It was found that aluminium can has less impact to the environment compared to the other two type of beverage packaging. If based on the CML eleven impact categories, plastic bottle was rank as the most impactful towards the environment, followed by glass bottle and aluminium can as the least impactful. Other than that, it may probably due to the quantity of material being used, the effect of the material during processing, and the recyclable ability.